KINERJA GURU DALAM UPAYA PENGUATAN KARAKTER SISWA - Diajeng Inkris Fadhillah; Abdul Khoir HS (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
The study was conducted to find out how the teacher’s performance in an effort to strengthen thecharacter of students in Islamic Cultural History learning. Through inductive and comparative dataanalysis techniques, researchers seek to explain and interpret rationally, objectively and consistentwith the objectives and research problems. Strengthening character in Islamic Cultural History lessonsis certainly in line with character values that have been formulated by the Ministry of Education andCulture, but in Islamic Cultural History subjects there are also character values that refer to thenature of the Prophet. In implementing teacher performance, teachers try to master theory by applyinglearning principles well, in addition, through digital literacy media as a learning resource, teachersexplain about exemplary figures that can be used as models in efforts to strengthen student character.In addition to making Cultural History subjects less boring, this also spurred character strengtheningwhich was also formed by teachers through digital literacy, namely, the enthusiasm of students inusing digital as a source of knowledge.